PENGARUH SISTEM PENGENDALIAN INTERN, KEPATUHAN TERHADAP PERATURAN PERUNDANG-UNDANGAN, OPINI AUDIT TAHUN SEBELUMNYA DAN UMUR PEMERINTAH DAERAH TERHADAP PENERIMAAN OPINI WAJAR TANPA PENGECUALIAN PADA LAPORAN KEUANGAN PEMERINTAH DAERAH DI SELURUH INDONESIA - Sari, Ria Nelly (Jurnal Akuntansi (Media Riset Akuntansi & Keuangan), 2014)
The objectives of this research are to prove empirically by explaining the direct effectof the independent variable internal control system, compliance with laws andregulations, the previous years audit opinion and the age of the local governmentagainst acceptance of an unqualified opinion on the financial statements of the localgovernment. Internal control system variable is proxied by weakness of the systemof internal control that consist of the weaknesses of the system of accounting andreporting controls (SPAP), the weakness of the implementation of the control systemof income and expenditure budget (SPPAPB), the weakness of the internal controlstructure (StPI). As for the variable compliance with laws and regulations is proxiedby the number of cases and the value of non-compliance with statutory provisionsthat consist of findings that result in loss of the state, the potential loss to the state,lack of acceptance, administrative irregularities, not economic, ineffectiveness andinefficiency. The data analysis was conducted using logistic regression. Thepopulation in this study is the Local Government Finance Report in Indonesia in2008 - 2012 who obtained opinion from the BPK RI. The sample in this studyamounted to 2,144 LKPD throughout Indonesia. Data in this study were obtained onthe website www.http//bpk.go.id publications. www.wikipedia.org and www.kemendagri.go.id. The results of research shows that the weakness of controlsystem of accounting and reporting (SPAP), non-compliance with statutoryprovisions that result in the case of loss of regional/corporate and administrativeirregularities negative effect on WTP opinion acceptance. While the previous yearsaudit opinion positive effect on WTP opinion acceptance.Keywords: internal control system, compliance with laws and regulations,theprevious years audit opinion and the age of the local government,anunqualified opinion